2010
DOI: 10.1039/b913749a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting [2+2] cycloaddition chemistry: achievements with allenes

Abstract: The allene moiety represents an excellent partner for the [2+2] cycloaddition with alkenes and alkynes, affording the cyclobutane and cyclobutene skeletons in a single step. This strategy has been widely studied under thermal, photochemical and microwave induced conditions. More recently, the use of transition metal catalysis has been introduced as an alternative relying on the activation of the allenic component. On the other hand, the intramolecular version has attracted much attention as a strategy for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
162
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(166 citation statements)
references
References 175 publications
4
162
0
Order By: Relevance
“…45 min) to minimize competing intermolecular processes. [5,8] Lowering the reaction temperature decreased reaction efficiency (entry 9), and control experiments demonstrated that the phosphine ligand is required for efficient reactivity (entry 10). No reaction occurred in the absence of the nickel catalyst.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…45 min) to minimize competing intermolecular processes. [5,8] Lowering the reaction temperature decreased reaction efficiency (entry 9), and control experiments demonstrated that the phosphine ligand is required for efficient reactivity (entry 10). No reaction occurred in the absence of the nickel catalyst.…”
mentioning
confidence: 98%
“…However, these reactions currently require styrene [3] or diene [4] pcomponents and substituted allenes as reaction partners, thus limiting potential applications in complex synthesis. [5] A catalytic ene-allene [2+2] transformation with broad substrate scope, ideally using inexpensive first-row metals as catalysts, would constitute a highly attractive transformation for the stereoselective synthesis of complex cyclobutanes. In the course of previous work in our laboratory targeting nickel-catalyzed, complexity-generating [2+2+2] cycloadditions of alkenes and allenes, we observed the production of a [2+2] ene-allene cycloadduct as a minor byproduct with one of our substrates.…”
mentioning
confidence: 99%
“…The presence of afluorinated solvent is essential for the success of these reactions whichform unsymmetrical tri-and tetrasubstituted cyclobutanes through ah eterodimerization process involving two different alkenes.Wehave recently engaged in ap rogram of research aimed at exploring metal-free conditions for the oxidation of organic compounds.One of our objectives is the study of hypervalent iodine reagents and the contributions that they can make to organic synthesis.[1] In particular, we wanted to explore hypervalent iodine reagents as promoters of single-electron transfer (SET) [2,3] processes,b ecause we think it is an underdeveloped and underutilized area with significant potential for reaction discovery.O ne interesting SET-promoted reaction that captured our attention involves the formation of cyclobutanes [4,5] from electron-rich alkenes (notably styrenes).Theo xidation-promoted dimerization reaction of electron-rich alkenes was first reported by Ledwith and coworkers who used iron(III) and cerium(IV) to form aradical cation from an alkene.[6] Later work by Bauld et al showed the effectiveness of triaryl amine radical cations to oxidize alkenes. [7] In general, the oxidized form of an alkene (exemplified with 1a!A;S cheme 1) is proposed to react with another molecule of (unoxidized) alkene to form an oxidized cyclobutane intermediate (B)w hich then captures an electron to regain neutrality and form the product 2a.The source of the electron for the final step may be either the reduced form of the catalyst (i.e., as produced in the first step), or alternatively another molecule of alkene,t op ropagate the chain.…”
mentioning
confidence: 99%
“…9 Because the thermal process is not allowed by the Woodward-Hoffmann rules 10 and the Fukui´s frontier oribital theory, 11 most of the examples have been explained via a 45 stepwise diradical mechanism. However, when the reaction is catalyzed by a transition metal catalyst the reaction mechanism has been explained in terms of reductive elimination of metallacyclopentanes or metallacyclopentenes intermediates.…”
Section: Reactivity Allene-allenementioning
confidence: 99%